2013
DOI: 10.1016/j.bbmt.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo T Cell Costimulation Blockade with Abatacept for Acute Graft-versus-Host Disease Prevention: A First-in-Disease Trial

Abstract: We performed a first-in-disease trial of in vivo CD28:CD80/86 costimulation blockade with abatacept for acute graft-versus-host disease (aGVHD) prevention during unrelated-donor hematopoietic cell transplantation (HCT). All patients received cyclosporine/methotrexate plus 4 doses of abatacept (10 mg/kg/dose) on days -1, +5, +14, +28 post-HCT. The feasibility of adding abatacept, its pharmacokinetics, pharmacodynamics, and its impact on aGVHD, infection, relapse, and transplantation-related mortality (TRM) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 44 publications
1
95
0
2
Order By: Relevance
“…Unlike the hyperacute GVHD cohorts, recipients prophylaxed with combinatorial therapies (either with standard-of-care tacrolimus plus methotrexate [Tac/MTX], or Siro plus CTLA4-Ig [Siro/CTLA4-Ig]) 7,8 successfully suppressed hyperacute GVHD. Thus, in the first several weeks posttransplant, both the Tac/Mtx and Siro/CTLA4-Ig cohorts controlled the clinical symptoms of disease ( Figure 1B-C).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the hyperacute GVHD cohorts, recipients prophylaxed with combinatorial therapies (either with standard-of-care tacrolimus plus methotrexate [Tac/MTX], or Siro plus CTLA4-Ig [Siro/CTLA4-Ig]) 7,8 successfully suppressed hyperacute GVHD. Thus, in the first several weeks posttransplant, both the Tac/Mtx and Siro/CTLA4-Ig cohorts controlled the clinical symptoms of disease ( Figure 1B-C).…”
Section: Resultsmentioning
confidence: 99%
“…Both studies were institutional review board-approved and conducted between 2010 and 2013, as previously described. 23 Patient and transplant characteristics are shown in Table 1. Patients were analyzed prospectively for CMV reactivation by polymerase chain reaction (PCR), and those that reactivated CMV (.300 copies per mL whole blood) were treated with antiviral therapy according to institutional standards.…”
Section: Methodsmentioning
confidence: 99%
“…All patients received myeloablative pretransplant conditioning and unmanipulated unrelated-donor allografts. 23 Immune reconstitution was monitored in detail in all patients onstudy, and revealed an extremely wide variability in the pace and character of their immune reconstitution, for which the heterogeneity was most prominent in the CD8…”
Section: Patient Characteristics and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Further, addition of abatacept to CSA/MTX standard aGVHD prophylaxis was investigated in a pilot clinical trial involving 10 patients transplanted from unrelated donors. [91] Only two patients developed grade II-IV acute GVHD. A phase II multicentre randomized trial of abatacept combined with calcineurin inhibition and MTX after unrelated donor alloHSCT is currently ongoing in the United States (ClinicalTrials.gov#NCT01743131).…”
Section: Blockade Of Cytokine-induced Signal Transduction In T Cellsmentioning
confidence: 98%